THE VIEWS OF RELIGIUS AND COMMUNITY LEADERS ON DETERMINING THE QIBLA DIRECTION - Suciati, Aluh Suciati; Rizal, Ahmad Ashril (UIN ALAUDDIN MAKASSAR, 2024)
Abstract This study aims to determine the qibla direction at Masjid Besar Fathul Mubin in Jerowaru using the Istiwa’aini method and to understand the perspectives of religious and community leaders regarding the qibla direction based on this method. The research employs field research and a mixed-method approach to combine positivism and post-positivism. Data was collected through observation, interviews, and documentation from primary and secondary sources in Jerowaru Village, with analysis conducted interactively. The results reveal that views on the qibla direction at Masjid Besar Fathul Mubin originated from a recalibration conducted by the Ministry of Religious Affairs several years ago. However, this recalibration triggered debates among community leaders. Some accepted the recalibration results and sought to adjust the mosque's qibla direction accordingly, while others rejected the change, causing uncertainty in establishing the qibla direction. Of the six informants interviewed regarding the qibla issue in Jerowaru Village, three rejected the qibla adjustment because they believed that the measurements by their ancestors were accurate. In contrast, the other three informants agreed on recalibrating the qibla direction using modern tools and accurate methods. Efforts to address the qibla direction deviation could include recalibration by the Ministry of Religious Affairs or the Jerowaru Sub-district Office using modern astronomical tools, along with socialization and support to enhance understanding of the importance of precise qibla direction. Establishing the qibla direction based on recalibration results may provoke disputes among community and religious leaders who oppose it, leading to prolonged debates. However, failure to adjust the qibla could impact the validity of the prayers of Jerowaru residents, underscoring the importance of making a decisive resolution on this matter..